Speed, Spatial, and Temporal Tuning of Rod and Cone Vision in Mouse - Umino, Yumiko (Society for Neuroscience, 2008)
Rods and cones subserve mouse vision over a 100 million-fold range of light intensity (−6 to 2 log cd m(−2)). Rod pathways tune vision to the temporal frequency of stimuli (peak, 0.75 Hz) and cone pathways to their speed (peak, ∼12°/s). Both pathways tune vision to the spatial components of stimuli (0.064–0.128 cycles/°). The specific photoreceptor contributions were determined by two-alternative, forced-choice measures of contrast thresholds for optomotor responses of C57BL/6J mice with normal vision, Gnat2(cpfl3) mice without functional cones, and Gnat1(−/−) mice without functional rods. Gnat2(cpfl3) mice (threshold, −6.0 log cd m(−2)) cannot see rotating gratings above −2.0 log cd m(−2) (photopic vision), and Gnat1(−/−) mice (threshold, −4.0 log cd m(−2)) are blind below −4.0 log cd m(−2) (scotopic vision). Both genotypes can see in the transitional mesopic range (−4.0 to −2.0 log cd m(−2)). Mouse rod and cone sensitivities are similar to those of human. This parametric study characterizes the functional properties of the mouse visual system, revealing the rod and cone contributions to contrast sensitivity and to the temporal processing of visual stimuli.